Selection of GalNAc-conjugated siRNAs with limited off-target-driven rat hepatotoxicity - Maja M. Janas; Mark K. Schlegel; Carole E. Harbison; Vedat O. Yilmaz; Yongfeng Jiang; Rubina Parmar; Ivan Zlatev; Adam Castoreno; Huilei Xu; Svetlana Shulga-Morskaya; Kallanthottathil G. Rajeev; Muthiah Manoharan; et al. (Nature Communications, 2018)
A subset of chemically-modified siRNAs conjugated to trivalent GalNAc may fail during nonclinical development due to rat hepatotoxicity. Here, the authors show that hepatotoxicity may be accounted for by microRNA-like off-target effects of siRNA and can be mitigated by a thermally destabilizing modification in the siRNA seed region.